Investigations on lignite use for lead removal from aqueous solutions under static and dynamic conditions: adsorption properties and mechanism exploration - Mlayah, Ammar; Jellali, Salah; Azzaz, Ahmed Amine; Jeguirim, Mejdi; Sellalmi, Haykel; Hamdi, Noureddine (Comptes Rendus. Chimie, 2021)
Lignite, as an abundant and low-cost material, was tested for lead (Pb(II)) removal from aqueous solutions under various experimental conditions for both static (batch) and dynamic (column) experiments. Static assays showed that Pb(II) removal efficiency increases with rising in its initial concentration, aqueous pH, and adsorbent dosage values. Adsorption kinetic and isothermal data were well fitted with the pseudo-second-order and Freundlich models, respectively, suggesting that lead removal by lignite is mainly governed by chemical processes and occurs heterogeneously on multilayer surfaces. The maximum Langmuir’s adsorption capacity was equal to 61.4 mg$· $g$^{-1}$, which is high in comparison to various natural materials. The laboratory column experiments showed that Pb(II) breakthrough curves and subsequent lignite adsorption efficiency is highly dependent on the bed height. Due to the short time contact between Pb(II) and lignite particles inside the column, the highest adsorption capacity was about 21%, which is lower than the one found in the batch mode. Even under dynamic conditions, lignite exhibits a high adsorption capacity compared to other adsorbents, which promotes its use as a low-cost and efficient material for Pb(II) and the removal of other heavy metals from wastewaters.